Antecedents of green creativity: the mediating role of employee green commitment and employee job satisfaction - Agus Sugiarto; Andrian Dolfriandra Huruta (Cogent Business & Management, 2023)
This research aims to analyze the direct and indirect effect of green human resource management (HRM), employee green commitment, and employee job satisfaction on green creativity. This research employed a questionnaire to collect samples from companies in Indonesia committed to going green. A total of 200 responses were collected for statistical analysis with Partial Least Square-Structural Equation Modeling (PLS-SEM). This research provides empirical evidence that the green HRM, employee green commitment, and employee job satisfaction have both direct and indirect (mediating) effects on the green creativity. These findings offer useful insights into green creativity practices in Indonesia, including the mediating role of employee green commitment and employee job satisfaction.
Keywords: 650; Componential theory of creativity; green HRM; green commitment; job satisfaction; green creativity